SOUND OF AL-QURAN THERAPY (SAQTY) ON THE PHYSIOLOGICAL FUNCTION OF PREMATURE INFANTS IN THE NICU - Warti Ningsih; Siti Rofiatun Rosida (P3M Universitas 'Aisyiyah Surakarta, 2023)
Introductory summary: Premature infants is unstable individual. The first treatment contributes to the next quality of life for premature infants. Sound stimulation with harmonious strains reduces sound stressors in the NICU Room. Objectives: This research aims to analyze the effect of Sound Of Al-Quran Therapy (SAQTY) on the physiological function of premature infants. Methodology: This study used Randomized Controlled Trial (RCT), 15 premature infants received SAQTY intervention, and 15 premature infants received nature sounds. The intervention was given for six days with a duration of 30 minutes with 50-60dB as measured by Sound Level. Sampling used accidental sampling, and the statistical test used was paired T-Test. Results: Data collection was carried out three times, the first day before treatment, the third day and the sixth day. The results of the p-value in the intervention group for heart rate, temperature, respiratory rate, oxygen saturation on the third day (0.001; 0.002; 0.002; 0.034) and the sixth day (0.000; 0.000; 0.001; 0.002) overall p-value <0.05 . Conclusion: SAQTY has a good effect on the physiology of premature infants who are treated in the NICU. SAQTY provides relaxation that makes infants have better sleep quality so that they can become physiologically stable.